2021
DOI: 10.1002/saj2.20224
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical and hydrological properties as affected by a five‐year history of poultry litter applied to a cotton–corn–soybean rotation system

Abstract: Few studies were conducted to ascertain poultry litter (PL) and its residual influence on soil physical and hydrological properties. A field study was conducted on a sandy loam soil for 8 yr in corn (Zea mays L.), cotton (Gossypium hirsutum L.), and soybean [Glycine max (L.) Merr.] rotations at Mississippi Agricultural and Forestry Experiment Station in Verona, MS. Poultry litter treatment was applied to the three crops at an average of 7.6 Mg ha -1 yr -1 in the first 5 yr. The inorganic fertilizer treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…Feng et al [33] illustrated that poultry litter addition significantly increased plant available water content by 20%. Singh et al [34] indicated that long-term application of cattle manure and fertilizer increased soil porosity compared with no fertilizer at the microscale level in maize-soybean rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al [33] illustrated that poultry litter addition significantly increased plant available water content by 20%. Singh et al [34] indicated that long-term application of cattle manure and fertilizer increased soil porosity compared with no fertilizer at the microscale level in maize-soybean rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Total C constituted the greatest fraction of both litter sources, with about 34% and 46% of the total dry matter in PL1 and PL2, respectively. Because of the high content of total C in litter, its land application may improve soil quality and crop production by increasing soil organic carbon and consequently enhancing soil aggregation and aggregate stability, increasing soil porosity and WHC, improving hydraulic properties of soil, and increasing soil microbial community (Adeli et al 2007;Yang et al 2019;Feng et al 2021).…”
Section: Composition Of Poultry Litter As a Soil Amendmentmentioning
confidence: 99%
“…Because poultry litter is loaded with high amounts of nutrients essential for plant growth, such as nitrogen (N), phosphorus (P), and potassium (K) (Ashworth et al 2020), it has traditionally been applied to agricultural land as an organic fertilizer (Sharpley et al 2009). Application of poultry litter to croplands is shown to improve soil fertility, earthworm and microbial communities, as well as soil physical and hydrological properties such as aggregate stability, infiltration rate, and hydraulic conductivity (Adeli et al 2009;Ashworth et al 2018;He et al 2019;Feng et al 2021). However, long-term land application of poultry litter has been shown to accumulate nutrients and trace metals in soil (Daigh et al 2009), and through runoff and leaching it has the potential to impair surface and groundwater quality (Sharpe et al 2004;Bolan et al 2010;McMullen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of crop rotation on soil physical properties are widely reported [9][10]. For example, when legumes are introduced in a crop rotation, macro aggregate formation increases because of deep roots, leaf drop, increased rhizosphere activity, and root exudates [11].…”
Section: Introductionmentioning
confidence: 99%